What Is the Carbon Origin of Early-Wood?. Issue 5 (19th November 2018) - Kudsk, Sabrina G K; Olsen, Jesper; Nielsen, Lasse N; Fogtmann-Schulz, Alexandra; Knudsen, Mads F; Karoff, Christoffer
ABSTRACT: Substantial amounts of annual radiocarbon ( 14 C) data have recently been produced with the purpose of increasing the time resolution of 14 C records used for constructing the calibration curve and for studying the occurrence of abrupt cosmic-ray events. In this study, we investigate if it is possible to resolve sub-annual scale changes in the atmospheric 14 C content by measuring radiocarbon in early-wood and late-wood fractions from Danish oak. The tree-ring samples span the period 1954–1970 CE, hereby covering the peak of the bomb pulse. A least squares test comparing the atmospheric 14 C content and the new sub-annual 14 C record from Danish tree rings reveals that by measuring early-wood and late-wood fractions, it may be possible to resolve sub-annual variations in past atmospheric 14 C levels.